(untitled) (Revista Contexto & Educação, 2020)
This article presents the results of the research on the impact of the training program in emotional education of the Núcleo de Educação Emocional (NEEMOC-UFPB), conducted in the municipal school network, in the city of Queimadas-PB, Brazil. Based on the teachers’ perceptions, qualitative research of a phenomenological nature produced data, through a testimonial and questionnaire, and considered as theoretical presuppositions the work of Mayer and Salovey (2015), Bisquerra (2000), Damásio (2017) and Possebon (2018), among others. We obtained as results, from the teacher’s perception, a set of evidences that indicate the power of the theoretical-experiential methodology of the training course. In summary, the proposal of the emotional experience seems to overcome in efficiency the approaches of emotional intelligence and emotional competence.